ANALISIS DIMENSI ELECTRONIC WORD OF MOUTH (EWOM) DAN PENGARUHNYA TERHADAP MINAT KUNJUNGAN PADA OBYEK WISATA DI MALANG RAYA - Diana Eka Poernamawati (Adbis: Jurnal Administrasi dan Bisnis, 2018)
This study analyzes the influence of the Electronic Word Of Mouth (Ewom) variable on interest in visits to tourism objects in Malang. The analytical tool used in this study is the analysis of multiple regression. The results showed that the intensity variables and content variables did not significantly influence, with the results of the calculation of t-hitung smaller than t-table. While the Valence of Opinion variable has a significant positive effect with the results of t-hitung 4.205 greater than t-table 1.993. Multiple regression analysis produces Fhitung has a value of 19.408 greater than F-table, which is 2.73. Thus, it can be said that the intensity variable, valence of opinion variable and content variable simultaneously influence the interest of the visit.